(untitled) (Scientific journal of the Fergana State University, 2026)
The use of digital tools in teacher education has gained increasing attention as educational systems strive to align with XXI century demands. This study investigates the integration of digital tools in teacher training programs and their impact on developing methodological competencies and improving classroom outcomes. The research adopts a mixed-methods approach, combining surveys and observational studies to evaluate the effectiveness of digital tools. The findings highlight significant improvements in teacher competencies and student engagement, while also identifying challenges related to resource allocation and teacher readiness. Recommendations for optimizing digital tool integration are discussed.